APPLICATION OF MODERN EDUCATIONAL TECHNOLOGY IN THE PROCESS OF PREVENTION AND OVERCOMING OF STUDENTS’ MORAL ALIENATION - Zalina K. Malieva (Высшее образование в России)
This article describes the features of the application of modern educational technologies in the process of forming of such necessary qualities for a modern specialist as social competence, communication skills, critical thinking skills, the ability to reflect and adequate perception of the events, other people and themselves, that would contribute to the prevention and overcoming of students’ moral alienation. The paper discusses the essence and diversity of modern interactive teaching technologies, the advantages of project method, possibilities of telecommunication training projects. It also provides the examples of practical realization of modern interactive technologies in the educational-upbringing process of the North%Ossetian State University. The results of the study extend the knowledge about the nature and possibilities of modern educational technologies, which facilitates students’ spiritual and moral development.